Physicochemical, antimicrobial and antioxidant properties of chitosan/TEMPO biocomposite packaging films. (September 2018) - Soni, Bhawna; Mahmoud, Barakat; Chang, Sam; El-Giar, Emad M.; Hassan, El Barbary
Highlights: Chitosan/TEMPO-CNFs biocomposite films with several composition were prepared. Antioxidant and antimicrobial properties were investigated for all kinds for films. Films with higher chitosan content showed great antimicrobial activity against food pathogenic bacteria. Antioxidant activities significantly improved with increasing chitosan percentage in the films. Abstract: Chitosan-based biocomposite films have attracted considerable attention due to their versatile physicochemical properties, and higher antimicrobial and antioxidant activities. This study investigated the physiochemical properties and examined the antimicrobial and antioxidant activities of chitosan/TEMPO (2, 2, 6, 6-tetramethylpiperidine-1-oxyl radical) bio-composite films. The films were prepared by incorporating different ratios of chitosan (100, 85, and 75 wt.%), TEMPO cellulose nanofibers (0, 15, and 25 wt.%) and sorbitol (25 wt.%). The bio-composite films were casted in an oven at 40 °C for 2–4 days. The successful incorporation of chitosan was confirmed by Fourier transform Infrared spectroscopy (FTIR) and thermal stability (TGA) measurements. The antimicrobial activity results showed a significant reduction in the growth of Salmonella enterica, E. coli O157:H7, and Listeria monocytogenes bacteria on the surface of the films with the proportional increase of chitosan. Results also showed a significant increase in the antioxidant activity of films with high chitosan concentration. The improved antimicrobial and antioxidant activities indicate that such films can be used successfully as packaging materials for several foods.